Smart Kampung, Mereduksi Birokratisasi Pelayanan Publik (Studi pada Desa Wringinrejo, Kecamatan Gambiran, Kabupaten Banyuwangi) - Abdul Aziz, Nana; Putri, Novi Permata (Jurnal Ilmiah Administrasi Publik, 2021)
Smart Kampung program is a program that is applied throughout the village within the scope of the Banyuwangi Regency Government. The program utilizes Information Technology (IT) to make it easier for people to get public services. This research aims to describe and analyze the implementation of services, especially in terms of population administration through the Smart Kampung program in Wringinrejo Village. Qualitative descriptive methods became the most rational choice in research, and data analysis was conducted with the interactive models of Miles, Huberman and Saldana. Data collection is done by observation, interview and documentation.The simple conclusion of this study shows that the implementation of public services through the Smart Kampung program is still not optimal given the lack of education to the community about the ease of the public service process through Smart Kampung, and the lack of details of budget utilization.